The Effect of Partly Replacing Vegetable Fat with Bovine Milk Fat in Infant Formula on Postprandial Lipid and Energy Metabolism: A Proof‐of‐principle Study in Healthy Young Male Adults. Issue 9 (1st April 2021) - Hageman, Jeske H.J.; Erdõs, Balázs; Keijer, Jaap; Adriaens, Michiel; de Wit, Britt; Stañková, Barbora; Tvrzická, Eva; Arts, Ilja C.W.; Nieuwenhuizen, Arie G.
Abstract : Scope: Infant formula (IF) uses besides vegetable fats also bovine milk fat, which differs in triacylglycerol (TAG) structure. Furthermore, it differs in fatty acid (FA) composition. Whether changing fat source in IF affects postprandial energy metabolism, lipemic response, and blood lipid profile is unknown. Methods and Results: A proof‐of‐principle study, with a randomized controlled double‐blind cross‐over design, is conducted. Twenty healthy male adults consumed drinks with either 100% vegetable fat (VEG) or 67% bovine milk fat and 33% vegetable fat (BOV), on 2 separate days. For a detailed insight in the postprandial responses, indirect calorimetry is performed continuously, and venous blood samples are taken every 30 min, until 5 h postprandially. No differences in postprandial energy metabolism, serum lipids, lipoprotein, or chylomicron concentrations are observed between drinks. After consumption of VEG‐drink, C18:2n‐6 in serum increased. Observed differences in chylomicron FA profile reflect differences in initial FA profile of test drinks. Serum ketone bodies concentrations increase following consumption of BOV‐drink. Conclusions: The use of bovine milk fat in IF does neither affect postprandial energy metabolism nor lipemic response in healthy adults, but alters postprandial FA profiles and ketone metabolism. Whether the exact same effects occur in infants requires experimental verification. Abstract : To study the effects of different fat sources in infant formula on energy and lipid metabolism, a proof‐of‐principle study with young adults is conducted. Replacing 67% of vegetable fat in infant formula with bovine milk fat did not affect postprandial energy metabolism nor the lipemic response, the initial difference in fatty acid profile of the formulas is reflected in the chylomicrons, and serum ketone bodies increase with consumption of bovine milk fat. Whether the exact same effects occur in infants requires experimental verification.